Solubility enhancement of poorly soluble antiretrovirals by novel self emulsifying drug delivery system - V. Vijay Kumar; J. Raju (International Journal of Pharmacy and Analytical Research, 2016)
Rilpivirine is a pharmaceutical drug used for the treatment of HIV infection. The drug is characterized with poor aqueous solubility and dissolution rate leading to low bioavailability of the drug. Hence, there is a need for the improvement of the solubility and dissolution of such drugs. The Aim of present study was to develop self emulsifying drug delivery system (SEDDS) for enhancement of solubility, dissolution rate and oral bioavailability of model drug Rilpivirine. Fifteen formulations were prepared using different oils, surfactants and co-surfactants. A pseudo ternary phase diagram was constructed to identify the self -micro emulsification region. Further, the resultant formulations were investigated for clarity, phase separation, drug content, % transmittance, globule size, freeze -thaw stability and in vitro dissolution studies. On the basis of dissolution profile and other above mentioned studies, F5 was found to be the best formulation of Rilpivirine S EDDS which contains Captex 355(Oil), Kolliphor RH 40 (Surfactant) and PG (Co -surfactant).